Firm Size as a Moderator in the Relationship Between Leverage, Cash Flow, Profitability, and Cash Holding: Evidence from Indonesia’s Food and Beverage Sector - Maryanti, Eny; Nabila, Ainun Mala; Hermawan, Sigit; Rahayu, Ruci Arizanda (Politeknik Ganesha Medan, 2026)
Cash holding plays a crucial role in maintaining corporate liquidity and financial flexibility, especially in capital-intensive industries such as food and beverage manufacturing. This study examines whether firm size moderates the relationship between leverage, cash flow, and profitability on cash holding in companies listed on the Indonesia Stock Exchange (IDX) during 2018–2022. The research employed a purposive sampling method, yielding 18 companies (57 firm-year observations). Data were analyzed using Ordinary Least Squares (OLS) and Moderated Regression Analysis (MRA) with SPSS 26. The results show that leverage (t = 3.217; p < 0.01) and cash flow (t = 2.948; p < 0.01) have a significant positive effect on cash holding, while profitability (t = 0.842; p > 0.05) has no significant impact. The R² value of 0.623 indicates that the independent variables explain 62.3% of the variation in cash holding. Furthermore, firm size significantly moderates the effects of leverage and cash flow, but does not moderate the relationship between profitability and cash holding. These findings highlight that larger firms tend to manage cash more effectively when facing leverage pressure or high cash flow, strengthening the understanding of liquidity management behavior in Indonesia’s manufacturing sector.